Water Diplomacy and Non-Traditional Security: Iraq's Efforts to Overcomes the Water Crisis - Heriamsal, Krisman; Heatubun, Rivelda Pricilia; Jekaisa, Heyna; Adikusuma , Andi Ira Tenri (Nation State: Journal of International Studies, 2024)
The water scarcity crisis in Iraq has become a non-traditional security issue that threatens the country's social, political and economic stability. According to international data, water scarcity is predicted to worsen by 2030, affecting more than 700 million people worldwide. Iraq, which depends on the flow of the Tigris and Euphrates rivers, is experiencing a decline in water quality and quantity that is worsening agricultural conditions, increasing social tensions and causing internal migration. This article analyzes the Iraqi government's efforts to address the water crisis through diplomacy by joining the Paris Agreement and the UN Water Convention, as well as organizing the Baghdad International Water Conference. This research uses a descriptive qualitative approach to explore the impact of water scarcity in Iraq and the diplomatic responses undertaken for mitigation. Although formal diplomacy has resulted in international aid and mitigation projects, climate change impacts and domestic governance issues, such as corruption, hamper the effectiveness of such efforts. This article also suggests the need for non-formal diplomacy involving non-state actors to improve the effectiveness of solving the water crisis in Iraq.